Exploring the applicability of effectuation theory in distressed venture environments - Thabang Madigoe; Marius Pretorius (Acta Commercii, 2024)
Orientation: Once appointed, business rescue practitioners and turnaround professionals are faced with critical decision making of whether a distressed venture contains an opportunity as judged by reasonable prospect.